1997
DOI: 10.1063/1.119797
|View full text |Cite
|
Sign up to set email alerts
|

“Blue” temperature-induced shift and band-tail emission in InGaN-based light sources

Abstract: Electro- and photoluminescence spectra of high-brightness light-emitting AlGaN/InGaN/GaN single-quantum-well structures are studied over a broad range of temperatures and pumping levels. Blue shift of the spectral peak position was observed along with an increase of temperature and current. An involvement of band-tail states in the radiative recombination was considered, and a quantitative description of the blue temperature-induced shift was proposed assuming a Gaussian shape of the band tail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
308
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 523 publications
(344 citation statements)
references
References 12 publications
27
308
2
1
Order By: Relevance
“…280 K. This can be explained via the hopping processes of excitons through the localized states. 2,3,[15][16][17][18]21 When temperature increases from 10 K to T R!BL , weakly localized carriers are thermally activated and they hop towards other strongly localized states resulting in the initial red-shift of emission energy. With increasing temperature from T R!BL to T BL!R , localized carriers at lower energy levels will be strongly thermally activated to higher levels leading to the blue-shift of emission energy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…280 K. This can be explained via the hopping processes of excitons through the localized states. 2,3,[15][16][17][18]21 When temperature increases from 10 K to T R!BL , weakly localized carriers are thermally activated and they hop towards other strongly localized states resulting in the initial red-shift of emission energy. With increasing temperature from T R!BL to T BL!R , localized carriers at lower energy levels will be strongly thermally activated to higher levels leading to the blue-shift of emission energy.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 It should be noted that the ELOC intrinsically exists in InGaN alloys, irrespective of growth orientation employed. 2,3,11,[13][14][15][18][19][20][21] Zhang et al 14 have reported that (11 22) QWs exhibit larger localization depths than polar QWs (estimated from TR-PL measurements at 7 K). Recently, by temperature-dependent photoluminescence (TD-PL) measurements, a strong ELOC degree has been found in (11 22) In 0.2 Ga 0.8 N QWs that causes a blue-shift of the QW exciton emission with rising temperature from $200 K to 340 K, irrespective of excitation source used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several groups have discussed the blue shift of the photoluminescence (PL) peak energy in InGaN/GaN heterostructures with increasing carrier injection. The observed carrier dynamics has been described using models that attribute the behavior to either the reduction of the quantum-confined Stark effect due to in-well field screening [5,9,10] band-filling of the energy band tail states [11,12] or both [13,14]. The main reason that these studies have not been able to directly elucidate these complicated dynamics is because traditional time integrated PL and time-resolved PL measurements allow only the radiative recombination dynamics to be directly characterized.…”
Section: Introductionmentioning
confidence: 99%